Tumor biomarker conversion between primary and metastatic breast cancer: mRNA assessment and its concordance with immunohistochemistry - Stefanovic, Stefan; Deutsch, Thomas M.; Sinn, Peter; Domschke, Christoph; Hennigs, André; Sohn, Christof; Schütz, Florian; Schneeweiss, Andreas; Wallwiener, Markus (OncoTarget, 2017)
Biomarker changes between primary (PT) and metastatic tumor (MT) site may be significant in individualizing treatment strategies and can result from actual clonal evolution, biomarker conversion, or technical limitations of diagnostic tests. This study explored biomarker conversion during breast cancer (BC) progression in 67 patients with different tumor subtypes and metastatic sites via mRNA quantification and subsequently analyzed the concordance between real-time qPCR and immunohistochemistry (IHC). Immunostaining for estrogen receptor (ER), progesterone receptor (PR), HER2, and Ki-67 was performed on formalin-fixed, paraffin-embedded PT and MT tissue sections. RT-qPCR was performed using a multiplex RT-qPCR kit for ESR1, PGR, ERBB2, and MKI67 and the reference genes B2M and CALM2. Subsequent measurement of tumor biomarker mRNA expression to detect conversion revealed significant decreases in ESR1 and PGR mRNA and MKI67 upregulation (all p < 0.001) in MT compared to PT of all tumor subtypes and ERBB2 upregulation in MT from triple-negative PT patients (p = 0.023). Furthermore, ERBB2 mRNA was upregulated in MT brain biopsies, particularly those from triple-negative PTs (p = 0.023). High concordance between RT-qPCR and IHC was observed for ER/ESR1 (81%(κ 0.51) in PT and 84%(κ 0.34) in MT, PR/PGR (70%(κ 0.10) in PT and 78% (κ −0.32) in MT), and for HER2/ERBB2 (100% in PT and 89% in MT). Discordance between mRNA biomarker assessments of PT and MT resulting from receptor conversion calls for dynamic monitoring of BC tumor biomarkers. Overall, RT-qPCR assessment of BC target genes and their mRNA expression is highly concordant with IHC protein analysis in both primary and metastatic tumor.
Gesehen am 14.09.2018